Absolute Configuration and Selective Trypanocidal Activity of Gaudichaudianic Acid Enantiomers - Batista, Joao M. [UNESP]; Batista, Andrea N. L. [UNESP]; Rinaldo, Daniel [UNESP]; Vilegas, Wagner [UNESP]; Ambrosio, Daniela L. [UNESP]; Cicarelli, Regina Maria Barreto [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Kato, Massuo J.; Nafie, Laurence A.; Lopez, Silvia N.; Furlan, Maysa [UNESP] (Amer Chemical Soc, 2011)
Gaudichaudianic acid, a prenylated chromene isolated from Piper gaudichaudianum, has been described as a potent trypanocidal compound against the Y-strain of Trypanosoma cruzi. We herein describe its isolation as a racemic mixture followed by enantiomeric resolution using chiral HPLC and determination of the absolute configuration of the enantiomers as (+)-S and (-)-R by means of a combination of electronic and vibrational circular dichroism using density functional theory calculations. Investigation of the EtOAc extract of the roots, stems, and leaves from both adult specimens and seedlings of P. gaudichaudianum revealed that gaudichaudianic acid is biosynthesized as a racemic mixture from the seedling stage onward. Moreover, gaudichaudianic acid was found exclusively in the roots of seedlings, while it is present in all organs of the adult plant. Trypanocidal assays indicated that the (+)-enantiomer was more active than its antipode. Interestingly, mixtures of enantiomers stowed a synergistic effect, with the racemic mixture being the most active.